HUBUNGAN STRES AKADEMIK DENGAN DEPRESI PADA SISWA MIPA DI SMAN 4 DENPASAR - Luh Sudarsani; Ni Luh Putu Shinta Devi; I Gusti Ngurah Juniartha (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Full day school is one of the school systems that can increase academic burden so that it can trigger academic stress. Academic stress can cause depression if not handled properly. This study aimed to determine the relationship of academic stress with depression in Mathematics and Natural Sciences students at SMAN 4 Denpasar. Correlative descriptive is a design that is used with cross sectional approach. The study sample consisted of 230 people was selected using stratified random sampling technique. The questionnaire used was Educational Stress Scale for Adolescent (ESSA) and Beck Depression Inventory (BDI). Spearman test was used for data analysis and there was a significant moderate relationship with the direction of a positive found in this study (p value = 0.0001, r = 0.433). This shows the more severe academic stress, the more severe depression experienced by students. The school is expected to make research as a guideline to determine learning activities that are more effective, varied, and fun so that it can reduce academic stress and student depression.